Production of Dissolving Pulp from Oat Husks. Process Design with Techno-Economic and Environmental Assessment in a Life Cycle Perspective - Ulefors, Amanda (My University, 2022)
To face the environmental concerns arising in the world, a green industrial revolution is required. Presently, the textile industry highly contributes to these environmental concerns and, thus, needs to play its part in the revolution. Textile producing processes needs to be adapted to reduce their environmental impact and alternative raw material needs to be identified to contribute to a green, circular economy. Agricultural residues might be one part of the solution. In this thesis, the production of dissolving pulp for the textile industry, from the agricultural residue oat husks, is evaluated. By a techno-economic and environmental assessment, in a life cycle perspective, the purpose of this thesis is to assess the possibilities of implementing oat husks as a raw material for the production of dissolving pulp in industrial scale. The technical assessment has been performed by simulating a scale-up of a lab process in Aspen Plus, based on provided lab data and conducted mass and energy balances. The results from the simulation have been implemented as a life cycle inventory in the environmental assessment, which has been carried out as a prospective life cycle assessment in the software GaBi. Furthermore, the expected capital and operating costs for the potential plant as well as the break-even price of the pulp have been determined. Uncertainties in the results are seen mainly due to the chemical recovery not being part of the simulation of the process. The results from the techno-economic assessment as well as the environmental assessment indicate potential for oat husks as a favourable alternative raw material in the textile industry.
Keywords: textile; dissolving; pulp; circular; green; oat; husks; residue; scale-up